SEJARAH PENDIDIKAN ISLAM DI INDONESIA; PERSPEKTIF SEJARAH KRITIS IBNU KHOLDUN - Shoni Rahmatullah Amrozi (Universitas Islam Lamongan, 2020)
The history of Islamic education is inseparable from the internal and external influences on the development and growth of Islamic education, these two influences accumulatively converge into one and produce a whole form of Islamic education in Indonesia. On the other hand the existence of the history of Islamic education has also long been the subject of studies conducted by some historians, both from within and from abroad. There have been many research results that inform Islamic education in Indonesia in a complete and comprehensive form. Based on this fact, the study of the history of Islamic education needs to be analyzed and applied to be used as reference material and references by Muslims themselves to better understand the journey and growth of Islamic education itself reviewed in Ibn Khaldun's perspective.